Implementation of an experimental program for the moral injury prevention among future teachers during martial state - Kozihora, Mariia (Psychological Prospects Journal, 2022)
Purpose. The article examines the study of the concept of moral injury (MI) in scientific literature. The purpose of our research is to highlight and substantiate the experimental program of a special course for future teachers. Methods. In the article, we used the method of theoretical analysis and generalization and the method of a natural experiment for the implementation of the special course program for future teachers "Moral injury: diagnosis and prevention in future teachers during martial law". Students of the 3rd year of the educational degree "Bachelor" of specialty 013 Primary Education of the Communal Institution of Higher Education "Lutsk Pedagogical College of the Volyn Regional Council" took part in the research. The program is designed for one semester of 2022/2023. and includes 11 lectures and 5 practical classes. Results. The results of the analysis of scientific sources make it possible to state that MI at the current stage can occur not only in military personnel, but also in civilians, most often in medical workers and teachers. In Ukraine, there are no studies specifically related to MI among teachers, although this is a very relevant topic during the period of a large-scale war in the country. As part of the study of MI manifestations during the military conflict, we developed an experimental program for future teachers. Our special course is based on spiritually oriented cognitive process therapy. With MI, shame, anger, guilt, loss of faith can arise, and such moral concepts as mercy, forgiveness, prayer, repentance, justice can prevent this. For our work, we have chosen topics that are considered the most effective in this therapy: the concept of MI, events, the meaning of the event in a person’s life, spiritual resources, the concept of guilt and recognition of guilt, self-forgiveness, respect, spiritual partnership during the experience of MI, post-traumatic growth. During practical classes, students consider practical exercises to help students calm down and survive a traumatic situation. For daily use, we suggest using exercises to control your own emotions, communicate with others, resolve conflict situations; self-help techniques in extreme situations. Conclusions. The knowledge gained from the special course "Moral injury: diagnosis and prevention of future teachers during martial law" is useful, practical skills can be used in professional activities.